Coexistence of Spin-Lattice Relaxation and Phonon-Bottleneck Processes in Gd-III-Phthlocyaninato Triple-Decker Complexes under Highly Diluted Conditions - Horii, Yoji (WILEY-V C H VERLAG GMBH, 2022)
10.1002/chem.201905796